On Assuring Rights to Aggrieved Party in Concluding Pretrial Cooperation Contract - A. A. Suvorova (Сибирское юридическое обозрение, 2012)
The article is devoted to the problematic issues in relation to legal regulation of aggrieved party’s rights while concluding a pretrial cooperation contract. As a result of scientific discussion the author offers her own point of view concerning the problems of assuring rights in the process of criminal cases investigation in respect to the persons who concluded a pretrial contract.